2019
DOI: 10.1038/s41598-019-41740-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the secretome of activated pancreatic stellate cells on growth and differentiation of pancreatic tumour cells

Abstract: Pancreatic ductal adenocarcinoma (PDAC) exists in a complex desmoplastic microenvironment. As part of it, pancreatic stellate cells (PSCs) provide a fibrotic niche, stimulated by a dynamic communication between activated PSCs and tumour cells. Investigating how PSCs contribute to tumour development and for identifying proteins that the cells secrete during cancer progression, we studied by means of complex antibody microarrays the secretome of activated PSCs. A large number of secretome proteins were associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 66 publications
0
26
0
Order By: Relevance
“…Vonlaufen, Hwang, and Gao et al demonstrated that the cell supernatant of activated PSCs induced cancer cells proliferation and migration mediated by PDGF and SDF-1/CXCR [4,8,10]. It also found that PSCs significantly promoted the growth and metastasis of cancer cells by co-culturing PSCs Ivyspring International Publisher with pancreatic cancer cells [11,12]. Apte et al discovered that PSCs can induce tumor-promoting paracrine effects [13].…”
Section: Introductionmentioning
confidence: 99%
“…Vonlaufen, Hwang, and Gao et al demonstrated that the cell supernatant of activated PSCs induced cancer cells proliferation and migration mediated by PDGF and SDF-1/CXCR [4,8,10]. It also found that PSCs significantly promoted the growth and metastasis of cancer cells by co-culturing PSCs Ivyspring International Publisher with pancreatic cancer cells [11,12]. Apte et al discovered that PSCs can induce tumor-promoting paracrine effects [13].…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β signalling is also one of the most important features forming the CSC niche and promotes plasticity in PDAC [6]. The pancreatic stellate cells (PSC) within the tumour microenvironment represent the principal source of TGF-β1 [7,8], but still very little is known about the TGF-β1-mediated crosstalk between PSC and PDAC cells. While L1 cell adhesion molecule (L1CAM; CD171) was originally discovered in the nervous system due to its important function for axon guidance and cell migration [9][10][11][12][13][14][15], it has also been shown to be a crucial factor for tumour cell dissemination and metastasis in colorectal, breast, kidney and lung cancer [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent reports have studied the complex interactions between PSCs and cancer cells based on analysis of their secretomes [42,60,61]. This prompted us to investigate the composition of the secretome from the paired primary PCCs and PSCs by proteomics-based analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The high variability in migration induction by the various PSCs may reflect intertumoral heterogeneity. Several proteins secreted by PSCs including cytokines, growth factors, and ECM components are known to interact with the PCCs and to induce activation of various signaling pathways that lead to enhanced migration and proliferation of the cancer cells [19,25,41,42,63]. The secretome data from both PSCs and PCCs investigated for these proteins revealed that the extent of migration observed among various PCCs was directly proportional to the amount of ligands/substrate proteins secreted by PSCs as well as to the amount of receptor proteins from PCCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation